2018
DOI: 10.1002/jsc.2179
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational imitation and payment mode decisions in cross‐border acquisitions

Abstract: Acquiring firm imitates the payment method decisions made by prior foreign acquirers targeting the same host country in cross-border acquisitions. Information asymmetry and bounded rationality induces acquirers to imitate the decisions of other foreign firms in the similar context.Mimetic behavior of the firms is more salient when the acquiring firm belongs to a country with high uncertainty avoidance cultural attribute and when institutional uncertainty is high in host country. The hypotheses are tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…However, in the case of the transactions paid in cash, the shareholders of the target firm are immediately subject to a tax. Payments in cash provide a positive signal (Ross 1977) implying confidence of the acquirer on achieving post-acquisition performances (Chhabra and Popli 2018). In line with these results, findings suggest stock payments may be beneficial in cross-border deals whenever the target is located in a weak institutional environment and when cultural distance is significant (Cho and Ahn 2017).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, in the case of the transactions paid in cash, the shareholders of the target firm are immediately subject to a tax. Payments in cash provide a positive signal (Ross 1977) implying confidence of the acquirer on achieving post-acquisition performances (Chhabra and Popli 2018). In line with these results, findings suggest stock payments may be beneficial in cross-border deals whenever the target is located in a weak institutional environment and when cultural distance is significant (Cho and Ahn 2017).…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies on mergers and acquisitions demonstrated the importance of cash in both domestic and cross-border mergers and acquisitions (Sankar and Leepsa 2018;Xie et al 2017;Chhabra and Popli 2018). This means of exchange offers the advantage of maintaining the ownership structures unchanged.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In cash deals, targets are underpriced in actual terms (i.e., according to fundamentals), but they are underpriced in stock acquisitions as compared to buyers (Yook, 2003). Cash-financed deals in "M&As" deliver abnormal returns which are positive, while stockfinanced deals produce negative returns (Chhabra & Popli, 2018;de Bodt et al, 2018;Faccio & Masulis, 2005;Güven, 2020;Mann & Kohli, 2009;Smith & Kim, 1994).…”
Section: Factors That Impact Manda Successmentioning
confidence: 99%
“…Foreign entry by a firm involves most or all of the TMT members (Barkema & Shvyrkov, 2007;Hambrick, Cho, & Chen, 1996). To mitigate the risk due to information asymmetry, managers often imitate the decisions of the prior international acquirers (Chhabra & Popli, 2018;Malhotra, Morgan, & Zhu, 2018). Though the extant literature focuses on the impact of CEO characteristics (Herrmann & Datta, 2002, 2006 on firm internationalization, however, studies examining the impact of TMT composition on internationalization remain scant (Nielsen & Nielsen, 2011).…”
Section: Introductionmentioning
confidence: 99%